Feeling better : beat depression and improve your relationships with interpersonal psychotherapy - Stulberg, Cindy Goodman, 1954- (New World Library, 2018)
"A guide to overcoming clinical depression by using interpersonal psychotherapy (IPT), a behavioral therapy that promotes emotional well-being by improving human relationships. Written by two psychologists. Contains case histories and exercises"--